Effect of the Side‐Chain‐Distribution Density on the Single‐Conjugated‐Polymer‐Chain Conformation. Issue 18 (14th November 2013) - Hu, Zhongjian; Adachi, Takuji; Lee, Young‐Gi; Haws, Ryan T.; Hanson, Benjamin; Ono, Robert J.; Bielawski, Christopher W.; Ganesan, Venkat; Rossky, Peter J.; Vanden Bout, David A.
Abstract The spatial arrangement of the side chains of conjugated polymer backbones has critical effects on the morphology and electronic and photophysical properties of the corresponding bulk films. The effect of the side‐chain‐distribution density on the conformation at the isolated single‐polymer‐chain level was investigated with regiorandom (rra‐) poly(3‐hexylthiophene) (P3HT) and poly(3‐hexyl‐2, 5‐thienylene vinylene) (P3HTV). Although pure P3HTV films are known to have low fluorescence quantum efficiencies, we observed a considerable increase in fluorescence intensity by dispersing P3HTV in poly(methyl methacrylate) (PMMA), which enabled a single‐molecule spectroscopy investigation. With single‐molecule fluorescence excitation polarization spectroscopy, we found that rra‐P3HTV single molecules form highly ordered conformations. In contrast, rra‐P3HT single molecules, display a wide variety of different conformations from isotropic to highly ordered, were observed. The experimental results are supported by extensive molecular dynamics simulations, which reveal that the reduced side‐chain‐distribution density, that is, the spaced‐out side‐chain substitution pattern, in rra‐P3HTV favors more ordered conformations compared to rra‐P3HT. Our results demonstrate that the distribution of side chains strongly affects the polymer‐chain conformation, even at the single‐molecule level, an aspect that has important implications when interpreting the macroscopic interchain packing structure exhibited by bulk polymer films.